The Hunter, the Stag, and the Mother of Animals - Jacobson-Tepfer, Esther.
1 online resource (448 pages)
Keywords: Offers a stunning archaeological and art historical exploration of the changing traditions of belief in pre-Bronze and Bronze Age North Asia.